Exploring sarcasm detection in amyotrophic lateral sclerosis using ecologically valid measures - Staios, Mathew; Fisher, Fiona; Lindell, Annukka; Ong, Ben; Howe, Jim; Reardon, Katrina (Frontiers in Human Neuroscience, 2013)
Amyotrophic lateral sclerosis is a rapidly progressive condition involving degeneration of both upper and lower motor neurons. Recent research suggests that a proportion of persons with ALS show a profile similar to that of FTD, with this group of ALS patients exhibiting social cognitive deficits. Although social cognitive deficits have been partially explored in ALS, research has yet to investigate such changes using ecologically valid measures. Therefore, this study aimed to further characterise the scope of social cognitive and emotion recognition deficits in non-demented ALS patients using an ecologically valid measure of social cognition. A sample of 35 ALS patients and 30 age-and-education matched controls were assessed using the Addenbrooke’s Cognitive Examination, the Brixton Spatial Anticipation Test, and The Awareness of Social Inference Test, where participants were required to discriminate between various emotions and decipher socially challenging scenarios enacted in video vignettes. Participants with ALS showed significant difficulties in recognising both sarcastic and paradoxical sarcastic statements, but not sincere statements, when compared to controls. After controlling for executive difficulties, ALS patients still displayed significant difficulties on tasks that assessed their comprehension of both sarcastic and paradoxical sarcastic statements. The inability to read social cues and make social inferences has the potential to place significant strain on familial/interpersonal relationships in ALS. The findings of this study highlight the importance of employing a broader range of neuropsychological assessment tools to aid in early detection of frontal lobe impairment in non-demented ALS patients.